Job stress among nurses in public hospitals in Ratchaburi province,Thailand - Aoki M (2012)
A cross-sectional descriptive study was conducted to study job stress among nurses in public hospitals in Ratchaburi province, Thailand. The objectives were to describe the prevalence of job stress, the socio-demographic factors, the work characteristics and the social support, as well as to identify the associations between the independent variables and dependent variable. The subjects in this study were 194 nurses and data were collected from January to February, 2010. Descriptive statistics were used to explain the characteristics of the study variables and the chi-square test was used to identify the relationship between dependent and independent variables. The result showed slightly over a quarter of the respondents (26.2%) were categorized into the high-risk group for job stress. Moreover, job stress was found to be significantly associated with workload, work relationships and social support. More than 70% of the respondents thought that their workloads were heavy. It was also found that heavy workloads caused high stress to nurses. Over 60% of respondents thought their work relationships were good. The nurses who thought that they had good relationships at work had lower job stress. The proportion of the subjects who thought that social support was good and thought it was moderate were almost equal, whereas no one thought their social support was poor. The more support they received, the less job stress they experienced. This study revealed that appropriate workloads, work relationships and social support can reduce job stress. In order to decrease job stress, it is recommended that nurses’ workloads, work relationships and social support should be carefully considered and managed by hospital administrators with a view to reducing job related stress. ABSTRACT A cross-sectional descriptive study was conducted to study job stress among nurses in public hospitals in Ratchaburi province, Thailand. The aims were to describe the prevalence of job stress, the socio-demographic factors, the work characteristics and the social support, as well as to identify the associations between the independent variables and dependent variable. There were 194 nurses in this study and data were collected from January to February, 2010. The result showed slightly over a quarter of the respondents (26.2%) were categorized into the high-risk group. Job stress was found to have significant associations with workload, work relationships and social support. More than 70 percent of the respondents thought that their workloads were heavy. It was found that heavy workloads caused high stress to nurses. Over 60 percent of respondents thought their work relationships were good. The nurses who thought that they had good relationships at work had lower job stress. Slightly over half of the respondents (50.8%) thought that social support was good and 49.4 percent thought it was moderate, whereas no one thought their social support was poor. The more support they received, the less their job stress. With respect to age, the mean of effort/reward ratio for the 36 to 45 age group was highest (0.714), while the under 35 age group had the lowest mean (0.663). Single status nurses had a higher mean of effort/reward ratio (0.701) than married nurses (0.672). Regarding monthly income, the 30,000 to 35,000 bath group had the highest mean of effort/reward ratio (0.702), while the over 35,000 bath group had the lowest mean (0.672). With regard to nurse registration term and working duration at the hospital, the under 10 year group had the highest mean of effort/reward ratio (0.718 and 0.704 respectively) This study revealed that appropriate workloads, work relationships and social support can reduce job stress. In order to decrease job stress, it is recommended that nurse’s workloads, work relationships and social support should be carefully considered and managed with a view to reduce job related stress.